Use of Idiolek Minang-Indonesia Language By Indonesian Language Education Students Semester 5: Penggunaan Bahasa Idiolek Minang-Indonesia Oleh Mahasiswa Pendidikan Bahasa Indonesia Semester 5 - Faradilla Intan Sari (Journal of Vocational Education and Information Technology (JVEIT), 2020)
Language has a very important function for humans, especially the communication function. Languageis a tool of social interaction or a tool of human communication. The occurrence of diversity or variety of languages is not only the speakers who are not homogeneous, but also because the social interaction activities that they do are very diverse. Every activity requires that language diversity occur. This study aims to describe yhe idiolect language by the 5th semester Indonesian Language Education Study Program Students. The method used in the method used by researchers in collecting research data. Based on the explanation above, it can be concluded that the method used by the researcher in his research is a qualitative method with techniques that reveal clear facts about the symptoms that exist in a research object without any manipulation in accordance with the state of the object under study. The results of research on the use of the minang-Indonesian idiolect language by 5th semester Indonesia language education language students are researchers finding a problem from interviews that the resource person said when speaking in Indonesian there are letters that he emphasizes such as the letter E. Everyday he always communicates with friends using Minang language so when asked to speak Indonesian a little bit differently, the idolek he uses is still minang idiolek.